Complementarity of eastern and western hemisphere long-baseline neutrino oscillation experiments - Minakata, H.; Nunokawa, H.; Parke, S. (American Physical Soc, 2003)
We present a general formalism for extracting information on the fundamental parameters associated with neutrino masses and mixings from two or more long baseline neutrino oscillation experiments. This formalism is then applied to the current most likely experiments using neutrino beams from the Japan Hadron Facility (JHF) and Fermilab's NuMI beamline. Different combinations of muon neutrino or muon anti-neutrino running are considered. The type of neutrino mass hierarchy is extracted using the effects of matter on neutrino propogation. Contrary to naive expectation, we find that both beams using neutrinos is more suitable for determining the hierarchy provided that the neutrino energy divided by baseline (E/L) for NuMI is smaller than or equal to that of JHF, whereas to determine the small mixing angle, theta(13), and the CP or T violating phase delta, one neutrino and the other anti-neutrino are most suitable. We make extensive use of bi-probability diagrams for both understanding and extracting the physics involved in such comparisons.